2017
DOI: 10.1515/hukin-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Post Activation Potentiation of the Plantarflexors: Implications of Knee Angle Variations

Abstract: Flexing the knee to isolate the single joint soleus from the biarticular gastrocnemius is a strategy for investigating individual plantarflexor’s post activation potentiation (PAP). We investigated the implications of testing plantarflexor PAP at different knee angles and provided indirect quantification of the contribution of gastrocnemius potentiation to the overall plantarflexor enhancements post conditioning. Plantarflexor supramaximal twitches were measured in ten male power athletes before and after a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Likewise, or push-ups with sleds have a better PAPE effect when verified with sprints 64 . The joint excursion of the joints involved in the movements performed as a conditioning activity must also be close to that required in the subsequent performance to maximize the PAPE effect [67][68][69] . The recovery time between the conditioning activity and the verification test is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, or push-ups with sleds have a better PAPE effect when verified with sprints 64 . The joint excursion of the joints involved in the movements performed as a conditioning activity must also be close to that required in the subsequent performance to maximize the PAPE effect [67][68][69] . The recovery time between the conditioning activity and the verification test is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the depth of the squat, the greater the increase in CMJ performance, with more gluteal activation and more work produced. Gago et al 2017 68 examined post-activation strengthening on plantar flexors by testing at different knee angles. Ten male athletes performed supra-maximal contractions of the plantar flexors before and after maximal isometric plantar flexion (MVIC) with the knee flexed and extended.…”
Section: Range Of Motionmentioning
confidence: 99%
“…Further, an isokinetic dynamometer (Isomed 2000, D&R Ferstl GmbH, Hemau, Germany) was individually adjusted with the participants lying in the supine position with hip, knee, and ankle joints in neutral position (180°, 180°, and 90°, respectively). Previously, Gago et al ( 2017 ) recommended to use an extended knee position (i.e., 180°) for more pronounced PAP effects. The foot of the dominant leg was firmly attached to the lever arm of the dynamometer with its rotational axis at the level of the malleoli.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the conditions in which a single maximal isometric contraction affects the contractile performance of the human plantar flexor muscle is important for the training of power athletes (Gago et al 2014b). Post-activation potentiation (PAP), an acute enhancement of muscle contractile properties and performance subsequent to a maximal conditioning contraction, is linked to RLC phosphorylation (Gago et al 2014a(Gago et al , 2017. As these authors reported, PAP observed after a conditioning task coexists with fatigue and depends on strength level, muscle fiber type, and age.…”
Section: Conditioning Exercise Training Of Power Athletesmentioning
confidence: 99%